The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1117/12.46405
|View full text |Cite
|
Sign up to set email alerts
|

<title>Effect of silylation condition on the silylated image in the DESIRE process</title>

Abstract: In recent years, there have been a lot of studies on surface imaging techniques in which the single layer lithography process is utilized. They have advantages of capability of high resolution, wide focus latitude, small critical dimension(CD) variation on topography, as well as their process simplicity compared with multilayer lithography process.The DESIRE[1,2] process, one of the surface imaging process, also has the same advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…And through the analysis of the silylated region and resist sidewall, mechanism of sidewall protection was discussed. 3. EXPERIMENTAL and the mixture was introduced into the stainless-steel chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And through the analysis of the silylated region and resist sidewall, mechanism of sidewall protection was discussed. 3. EXPERIMENTAL and the mixture was introduced into the stainless-steel chamber.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study on the resist profile, it was indicated that pattern formation was strongly depended on the silylated layer and the degree of sidewall protection during dry-development [3]. Then, we studied the effect of sidewall protection under various process factors such as soft-bake, silylation, and various resist materials.…”
mentioning
confidence: 99%